Problematic Smartphone Use and Problematic Social Media Use: The Predictive Role of Self-Construal and the Mediating Effect of Fear Missing Out - Servidio, Rocco; Koronczai, Beatrix; Griffiths, Mark D.; Demetrovics, Zsolt (Frontiers in Public Health, 2022)
Problematic smartphone use (PSU) and problematic social media use (PSMU) are two interrelated constructs which have received significant research attention over the past decade. The present study investigated the relationship between self-construal (distinguished as independent and interdependent), PSU and PSMU with Fear of Missing Out (FoMO) as a mediating variable. The sample comprised 405 Italian students who completed standardized psychometric scales assessing the variables of the study. Bivariate correlations analysis showed that FoMO and independent self-construal was significantly and negatively associated. On the contrary, interdependent self-construal was significantly and positively associated with FoMO, PSU, and PSMU. Mediation analysis showed that FoMO mediated the relationship between self-construal and both PSMU and PSU, but at different levels. The results demonstrated that FoMO full mediated the relationships between interdependent self and PSU, whereas only partial mediation was found between interdependent self and PSMU. Therefore, taking these personality characteristics into account may help reduce dysfunctional behaviour associated with problematic technology use and promote psychological well-being among students. However, it is recommended that further studies replicate the proposed model by including other psychological constructs.